The notion of sunna: an eclectic reading in the ibadhi legacy - Ahmed al-Kindi, Ahmed Yahya; Iman Anke, Sandra Bouzenita (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper offers a cursory reading in the Ibadhi legacy, drawing on its diversity in place and time. It investigates the notion of sunna in its different meanings and connotations in this legacy, in the linguistic, usuli and fiqhi usage as well as at its intersections with hadith, athar and sira. The article documents the rich and independent legacy of the Ibadhi school. It concludes that, apart from minor particularities in technical terms and conceptualisation, there is virtually no difference as compared to other schools in the usage of the notion of sunna.